Pestivirus infection in reindeer (Rangifer tarandus) - Larska, Magdalena (Frontiers in Microbiology, 2015)
Reindeer species (Rangifer tarandus, Linneus 1758) includes wild and semi-domesticated ruminants belonging to Capreaolinae subfamily of Cervidae family reared in Eurasia (reindeer subspecies) and North America (caribou subspecies). Herding of reindeer has a great historical, socio-economic and ecological importance, especially to indigenous ethnic minorities. Infectious disease threats may therefore impact not solely the animal population driving it to further extinction and irreversible alterations to the wild environments of northern hemisphere, but also add to cultural changes observed as negative impact of globalization. Introduction of new technologies to control of reindeer migration between dwindling pasture areas and intensification of reindeer husbandry may facilitate the intra- and interspecies transmission of pathogens. The role of the reindeer as a potential BVDV reservoir has been studied, however the number of publications is rather limited. The observed seroprevalences of the virus varied significantly between different geographical regions with different epidemiological situation. Most frequently limited number of animals studied and the differences in the sensitivities and specificities of the diagnostic test used could have also influenced on the differences between the studies. No pestivirus has been ever detected in free-ranging reindeer, however a putative pestivirus strain named V60-Krefeld has been isolated from reindeer kept at a German Zoo in the 1990’s. The virus was characterized as border disease virus type 2 (BDV-2) closely related to German ovine strains. The cross-neutralization studies of the semi-domesticated reindeer sera from Sweden suggested infection with a strain related to BDV-1 or BDV-2. The available data indicates that reindeer might be infected by a endemic species-specific BDV-like strain. However, the interspecies transmission of BVDV from domestic animals should not be excluded, since the susceptibility of reindeer to BVDV-1 has been confirmed under experimental conditions.